Hypoglycemic, Antihyperglycemic, and Toxic Effects of Physalis peruviana L. Aqueous and Methanolic Leaf Extracts in Wistar Rats - Kasali, Félicien M.; Kadima, Justin N.; Tusiimire, Jonans; Agaba, Amon G. (Journal of Experimental Pharmacology, 2022)
Physalis peruviana L. (Solanaceae) is a plant widely used in traditional medicine systems to manage various diseases, including diabetes mellitus, which remains a global health problem in developing and developed countries. This study aimed to scientifically evaluate its antidiabetic bioactivity and short-term toxicity in rats. Methods: We prepared various doses (100, 200, 400 mg/kg) of aqueous and methanolic leaf extracts for the antidiabetic study, and a dose of 2000 mg/Kg was prepared for the acute toxicity test. The first group that evaluated the hypoglycemic effect consisted of forty normoglycemic Wistar rats aged 7–8 months old with a weighted average of 265.8 ± 24.6 g. The second group consisted of intraperitoneal glucose-loaded male animals to evaluate the antihyperglycemic effect. The third group contained two groups of normoglycemic female rats (n = 3), aged 3 and 4 months old (weight average: 187.45 ± 14.82 g), treated for 14 days with aqueous and methanolic extracts (2 g/kg b.w) to assess mortality and toxic effects. Blood samples were taken at 30, 60, 90, and 120 min posttreatment in hypoglycemic and antihyperglycemic evaluations. Glibenclamide (5 mg/kg) was used as a reference drug. The control animals in each group did not receive the extracts. Results: In hypoglycemic rats, 100 mg/kg of aqueous and methanolic extracts significantly lowered the fasting blood glucose level by 13.92% (p < 0.0001) and 21.95% (p < 0.01), respectively, compared to the control group. In glucose tolerance test group, methanolic extracts significantly reduced hyperglycemia by 54.55% (p < 0.0001), 46.50% (p < 0.0001), 39.78% (p < 0.0001) at 400, 200 and 100 mg/kg b.w, respectively, compared to control; aqueous extract 400 mg/kg reduced hyperglycemia by 39.44% (p < 0.05). At the 2000 mg/kg dose, leaf aqueous and methanolic extracts did not show any signs of intoxication and mortality. Conclusion: Crude aqueous and methanolic leaf extracts of P. peruviana ambrosioides appeared safe at 2000 mg/kg and have bioactivity in controlling the blood glucose levels, supporting their use in treating diabetes.
Keywords: Physalis peruviana; leaf extracts; antidiabetic bioactivity; toxicity; rats